ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PT GAJAH TUNGGAL TBK PERIODE 2014-2023 - Uswatun Hasanah; Reza Octovian (Al-Muzdahir : Jurnal Ekonomi Syariah, 2026)
This research aims to determine the financial performance of PT Gajah Tunggal Tbk for the 2014-2023 period by measuring financial ratio analysis. The method used in this research is a quantitative. Technical analysis uses liquidity ratios and profitability ratios by comparing financial reports from previous years compared to industry standards according to Kasmir and the average standards of similar companies listed on the Indonesian Stock Exchange. Research data collection was obtained from company financial reports and library studies related to this research. The population used is the financial report of PT Gajah Tunggal Tbk for the 2014-2023 period and the sample used is the balance sheet and profit and loss report from 2014-2023. The results of this research indicate that the financial performance of PT Gajah Tunggal Tbk for the 2014-2023 period in terms of liquidity ratios is compared using industry standards according to Kasmere in an Unhealthy condition, because the average value of the Current Ratio and Quick Ratio is still below the Cashmere industry standard, while the financial performance of PT Gajah Tunggal Tbk for the 2014-2023 period is compared with the average standard of similar companies, companies in an unhealthy condition because they are below the average of similar companies. Then looking at the profitability ratio compared to using industry standards according to Kasmir, it is in an unhealthy condition, because the average value of Return On Assets and Return On Equity is still below the Kasmir industry standard, while the financial performance of PT Gajah Tunggal Tbk for the 2014-2023 period is compared with the average standard of similar companies. The company is in an unhealthy condition because it is below the average of similar companies.